1984
DOI: 10.2134/jeq1984.00472425001300020003x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Nitrogenous Compounds in a Rhodic Paleudult Following Heavy Manure Application

Abstract: Agriculture faces the problem of animal manure disposal while maintaining crop yields and soil water quality. There is an economic advantage of manure disposal at elevated rates close to the source. This in turn increases the potential for groundwater contamination. This study was conducted to determine the effect of high rates of cattle and poultry manure application on the N balance and on the distribution of NH4+, NO3−, NO2−, and total N to a depth of 6 m in a Davidson clay loam soil (Rhodic Paleudult, clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
3
10
0
2
Order By: Relevance
“…The increase indicated a great potential benefit for increasing soil C by PL application. The accumulation of C contents in littered soil was consistent with some previous results (Kingery et al 1994;Gascho and Hubbard 2006) but in contrast to others (Cooper et al 1984;Jackson, Leonard, and Wilkinson 1975). The control soil had C/N ratios of 12.1, 9.1, and 7.0 in depths of 0-20, 20-40, and 40-60 cm, respectively (Figure 2).…”
Section: Hay Yields and Soil C Contentssupporting
confidence: 91%
“…The increase indicated a great potential benefit for increasing soil C by PL application. The accumulation of C contents in littered soil was consistent with some previous results (Kingery et al 1994;Gascho and Hubbard 2006) but in contrast to others (Cooper et al 1984;Jackson, Leonard, and Wilkinson 1975). The control soil had C/N ratios of 12.1, 9.1, and 7.0 in depths of 0-20, 20-40, and 40-60 cm, respectively (Figure 2).…”
Section: Hay Yields and Soil C Contentssupporting
confidence: 91%
“…This has been reported, for example, in USA (Cooper et al 1984), The Netherlands (Uunk 1991), and has also been observed in the UK (Lord 1992). Poultry manures are a problem because, compared to other organic manures such as pig or cattle slurries and farmyard manures, they have a high dry matter content (c 60%) and a concomitant large N concentration.…”
Section: Introductionsupporting
confidence: 60%
“…Ϫ -N concentrations as high as 350 and 450 mg kg Ϫ1 , respectively, at a 2.1 m depth after 4 years (Cooper et al, 1984). Jackson et al (1977) reported that NO 3 Ϫ -N concentrations at the 1.07-m depth in the profile were ≈ 15 mg L Ϫ1 for the 22.4 Mg ha Ϫ1 surface applied litter treatment and 100 mg L Ϫ1 for the 134.4 Mg ha Ϫ1 rate.…”
Section: Introductionmentioning
confidence: 99%